Beck’s Depression Inventory II Suicidal Ideation in Medical Students – Prevalence and Associated Factors - Keuch, Lea; Pukas, Lilith; Rabkow, Nadja; Ehring, Emilia; Kindt, Tordis; Rehnisch, Carolin; Pelzer, Angelina; Lamlé, Patricia; Watzke, Stefan (International Journal of Medical Students, 2023)
Background: Suicide is the second leading cause of death in 15- to 29-year-olds in Germany. Studies have shown that compared to the general population students are more affected by suicidal ideation, as one major indicator of an attempted suicide. This effect is observed all over the world, interestingly, it is also true for physicians. Therefore, we investigated whether medical students are at an even higher risk than their peers to develop suicidal ideation. Methods: N=1,103 medical students at a German university completed a self-reporting survey investigating socio-demographic, potential risk, and protective factors. The Beck’s Depression Inventory (BDI)-II Item 9 “Suicidality“ served as the dependent variable. Results: N=130 students (11.8% of the total sample) reported suicidal ideation within the last two weeks. Stepwise computed logistic regression models including all potential risk factors resulted in 40% explained variance. The most significant independent risk factors were the BDI-score, usage of tranquilizers, feeling lonely, insufficient time for hobbies and prior personal mental health issues, whereas focus enhancing drugs showed to be the only independent protective predictor. The BDI-II score correlated positively with the number of students suffering from suicidal ideation. Conclusion: The prevalence of suicidal ideation in our sample medical student population exceeds that of the general population greatly, confirming existing data and emphasizing the need to raise awareness and establish prevention programs.